1998
DOI: 10.1046/j.1365-3059.1998.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bean line pattern mosaic virus on the monocyclic components of rust and angular leaf spot of Phaseolus bean at different temperatures

Abstract: Monocyclic components (development rate during the incubation period or latent period, lesion density, lesion size and disease severity) of rust (Uromyces appendiculatus) and of angular leaf spot (Phaeoisariopsis griseola) in two bean (Phaseolus vulgaris) cultivars (Rosinha G-2 and Carioca), pre-infected or not with bean line pattern mosaic virus (BLPMV), were determined. Trials were conducted at temperatures in the range from 9 to 27ЊC for rust and from 12 to 30ЊC for angular leaf spot. Regardless of viral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 26 publications
0
26
0
14
Order By: Relevance
“…, in which Z represents the proportion of germinated conidia; T is the temperature ( o C); M is the wetness period (h); b 2 and b 4 are the minimum and maximum temperatures, respectively; b 5 is a shape parameter, that influences the temperature range around the optimum in which the curve stays near to maximum germination; b 7 is a rate parameter; and b 1 , b 3 , and b 6 are parameters from the model with no biological meaning (HAU & KRANZ, 1990;BASSANEZI et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…, in which Z represents the proportion of germinated conidia; T is the temperature ( o C); M is the wetness period (h); b 2 and b 4 are the minimum and maximum temperatures, respectively; b 5 is a shape parameter, that influences the temperature range around the optimum in which the curve stays near to maximum germination; b 7 is a rate parameter; and b 1 , b 3 , and b 6 are parameters from the model with no biological meaning (HAU & KRANZ, 1990;BASSANEZI et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental design was completely randomized with three replications used for each treatment. When determining the minimum, optimum and maximum temperatures for mycelial growth, the generalized Beta function was adjusted to the data collected in the latest evaluation, according to BASSANEZI et al (1998). The pathogenicity of Botrytis sp.…”
Section: Várias Doenças Podem Estar Associadas Com Figos Mas Recentementioning
confidence: 99%
“…maintained on PDA at different temperatures for 10 days, and adjustments on the generalized Beta distribution according to BASSANEZI et al (1998).White circles represent the repetitions of each tested temperature; black circles were clear-cut by the statistical analysis used. …”
Section: Várias Doenças Podem Estar Associadas Com Figos Mas Recentementioning
confidence: 99%
“…Some research has been published showing the effect of the preinfection of one disease on a second disease. A detailed study for this approach to interactions was presented by Bassanezi et al (1998) who investigated the effect of pre-infection with Bean line pattern mosaic virus (BLPMV) on some elements of Uromyces appendiculatus and Phaeoisariopsis griseola over a wide range of temperatures. Other studies have applied the de Wit replacement series technique to investigate the outcome of competitive interactions between two plant pathogens using the conidial production (Adee et al, 1990;Nolan et al, 1999).…”
Section: Interactions In Disease Dynamicsmentioning
confidence: 99%
“…Weber et al (1994), for instance, concluded for the two wheat pathogens Septoria nodorum and Erysiphe graminis that wherever the two pathogens occur together, neither their dynamics, nor the influence of external factors could be understood, if interspecific interactions are neglected. Interactions may have significant implications for assessing crop losses, diagnosing the causes of these losses and for selecting appropriate management strategies, as well as for forecasting, modelling and simulations of epidemics (Waller & Bridge, 1984;Bassanezi et al, 1998). Estimates of yield losses caused by several diseases made by adding of single disease yield-loss models are likely to be inaccurate if interactions are occurring (Zhou et al, 2000).…”
Section: Introductionmentioning
confidence: 99%